The effects of women on corporate boards on firm value, financial performance, and ethical and social compliance - Isidro, H.; Sobral, M. (Journal of Business Ethics, 2015)
The European Commission has recently proposed the introduction of legally binding quotas for women on corporate boards of European companies. This proposal has put the spotlight on the question of whether increasing female representation on the board brings economic benefits to the firm. In order to shed light on the issue, this study investigates the direct and indirect effects of women on the board on firm value. We use a simultaneous equation model to estimate the effects of women on the board on firm value, financial performance, and compliance with ethical and social principles adopted by the firm. We find no evidence that a higher female representation on the board directly affects firm's value. However, we find indirect effects. Women on the board are positively related with financial performance (measured in terms of return on assets and return on sales) and with ethical and social compliance, which in turn are positively related with firm value. The findings in this study suggest that greater female representation on corporate boards of large European firms can increase firm value indirectly. Further, part of the indirect effect comes from stronger compliance with ethical principles, something that is not captured by accounting-based financial performance.